Canine antibody response to Phlebotomus perniciosus bites negatively correlates with the risk of Leishmania infantum transmission - Vlkova, Michaela; Rohousova, Iva; Drahota, Jan; Stanneck, Dorothee; Kruedewagen, Eva Maria; Mencke, Norbert; Otranto, Domenico; Volf, Petr (PLoS neglected tropical diseases, 2011)
BACKGROUND: Phlebotomine sand flies are blood-sucking insects that can transmit Leishmania parasites. Hosts bitten by sand flies develop an immune response against sand fly salivary antigens. Specific anti-saliva IgG indicate the exposure to the vector and may also help to estimate the risk of Leishmania spp. transmission. In this study, we examined the canine antibody response against the saliva of Phlebotomus perniciosus, the main vector of Leishmania infantum in the Mediterranean Basin, and characterized salivary antigens of this sand fly species. METHODOLOGY/PRINCIPAL FINDINGS: Sera of dogs bitten by P. perniciosus under experimental conditions and dogs naturally exposed to sand flies in a L. infantum focus were tested by ELISA for the presence of anti-P. perniciosus antibodies. Antibody levels positively correlated with the number of blood-fed P. perniciosus females. In naturally exposed dogs the increase of specific IgG, IgG1 and IgG2 was observed during sand fly season. Importantly, Leishmania-positive dogs revealed significantly lower anti-P. perniciosus IgG2 compared to Leishmania-negative ones. Major P. perniciosus antigens were identified by western blot and mass spectrometry as yellow proteins, apyrases and antigen 5-related proteins. CONCLUSIONS: Results suggest that monitoring canine antibody response to sand fly saliva in endemic foci could estimate the risk of L. infantum transmission. It may also help to control canine leishmaniasis by evaluating the effectiveness of anti-vector campaigns. Data from the field study where dogs from the Italian focus of L. infantum were naturally exposed to P. perniciosus bites indicates that the levels of anti-P. perniciosus saliva IgG2 negatively correlate with the risk of Leishmania transmission. Thus, specific IgG2 response is suggested as a risk marker of L. infantum transmission for dogs.
Keywords: Italy; imunoglobulin G; psi; Leishmaniasis; Dogs; Risk Assessment; Mass Spectrometry; Německo; Dog Diseases; Leishmania infantum; Phlebotomus; slinné proteiny a peptidy; western blotting; leishmanióza; Blotting, Western; Immunoglobulin G; Salivary Proteins and Peptides; nemoci psů; ELISA; ženské pohlaví; zvířata; hodnocení rizik; hmyzí proteiny; Germany; Insect Bites and Stings; kousnutí a bodnutí hmyzem; Itálie; Enzyme-Linked Immunosorbent Assay; Female; Insect Proteins; hmotnostní spektrometrie; Animals